Mathematics Learning Outcomes Through Puzzle-Based Student Teams Achievement Division: Hasil Pembelajaran Matematika Melalui Tim Siswa Berbasis Teka-teki dalam Pembagian Prestasi - Isfalara; Puput Wahyu Hidayat; Apdoludin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mathematics is a fundamental discipline that supports technological advancement and cognitive development, yet it remains challenging for many elementary students due to its abstract nature. Specific Background: Observations at SDN 12/II Empelu revealed that Grade IV students showed low learning outcomes, with 47% failing to reach the minimum mastery criteria, largely due to conventional teacher-centered approaches and lack of engaging media. Knowledge Gap: Previous studies have examined the effectiveness of cooperative learning models such as Student Teams Achievement Division (STAD) or visual aids like puzzles separately, but few have integrated both strategies to address students’ conceptual and motivational difficulties in mathematics. Aims: This study aimed to improve mathematics learning processes and outcomes by combining the STAD model with puzzle media. Results: Conducted as Classroom Action Research in two cycles with 17 students, the findings indicated increased teacher performance (85% to 97%), student activeness (67% to 85%), and cognitive achievement (67% to 84%). Novelty: The research demonstrates the effectiveness of integrating STAD with puzzle media in mathematics learning within the Merdeka Curriculum, a combination not extensively studied in rural elementary contexts. Implications: This approach provides an innovative and practical strategy for fostering active, collaborative, and meaningful learning, offering a model that can be adapted for other mathematical topics and primary education settings.Highlight : STAD with puzzle media improved the learning process and student activeness. Teacher performance increased from good to very good between cycles. Student learning outcomes rose significantly from 67% to 84%. Keywords : STAD, Puzzle Media, Mathematics, Learning Outcomes, Cooperative Learning